2011
DOI: 10.1080/01411921003671755
|View full text |Cite
|
Sign up to set email alerts
|

Who succeeds in advanced mathematics and science courses?

Abstract: Few students (particularly few girls) currently choose to take their Final School Examination (FSE) in advanced mathematics, chemistry and physics, a combination of subjects that is the best preparation for a science-oriented study in higher education. Are these subjects attainable by more students than is currently the case? This study examined 6033 students in upper secondary education, including 720 students who took their FSE in advanced mathematics, chemistry and physics. The results show that the latter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
(150 reference statements)
1
8
0
Order By: Relevance
“…It appears that a positive math self-concept requires a higher degree of security from girls than from boys. The only study we have seen that takes an analogous approach yielded similar results (Korpershoek et al, 2011). As in our study, high school students in the Netherlands selected sections to take as part of their final school examination.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It appears that a positive math self-concept requires a higher degree of security from girls than from boys. The only study we have seen that takes an analogous approach yielded similar results (Korpershoek et al, 2011). As in our study, high school students in the Netherlands selected sections to take as part of their final school examination.…”
Section: Discussionsupporting
confidence: 62%
“…Boys do better on mathematical subtests of cognitive tests (Strand et al, 2006;Lohman, Lakin, 2009) and outperform girls on national math tests (Hyde et al, 1990;Else-Quest, 2010;Lindberg et al, 2010) as well as international mathematics competency tests (Mullis et al, 2008;Nosek et al, 2009). There are also more boys in the highest-scoring groups (Benbow & Stanley, 1980;Benbow, C. P., 1988;Wai et al, 2010;Korpershoek et al, 2011).…”
Section: Sex Differences In Mathematical Achievement Measuresmentioning
confidence: 99%
“…In the Netherlands, only the "highest-achieving girls pursued" (p. 374) science and technology tertiary entrance classes in school (Korpershoek et al 2010). In Western Australia, the low numbers of females taking tertiary entrance physics seems to mirror this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have supported the observation that male students usually outperform female students in assessments particularly in the areas of mathematics and science (Abedlaziz, Ismail, & Hussin, 2011;Korporshoek, Kuyper, van der Werf, & Bosker, 2011). The analysis of a number of large assessments has demonstrated that male students generally performed better than did female students (Beller & Gafni, 1991).…”
Section: Gendermentioning
confidence: 91%